Diaphyseal Screw Prominence in Distal Radius Volar Plating - Eng, Kevin; Gil, Stephen; Page, Richard (Journal of Wrist Surgery, 2020)
Background Volar plating for distal radius fractures has become common. Screw prominence on the dorsal side from long screws can lead to tendon injury. Methods for detecting screws that penetrate the far cortex involve X-ray or ultrasound. These have focused on the distal row of screws. No studies have addressed screw penetration in the diaphysis. We describe two cases where diaphyseal screws caused symptoms. We then insert screws in the diaphysis of synbones 2 mm longer than measured and determine what angle of pronation or supination was best to detect this on X-ray.Methods Three synbones were plated using Synthes volar plate. The three diaphyseal screws were drilled perpendicular to the plate, and the depth measured. Cortical 2.4-mm screws were inserted, 2 mm longer than measured. The three synbones were then placed in a custom clamp to measure rotation. Lateral X-rays were taken at 0 degree rotation, and 5, 10, and 15 degrees of supination and pronation. The prominence of each screw was measured using the synapse digital ruler.Results For the screws that were placed at a neutral angle (perpendicular to the plate) the maximum visualization of the prominent tips occurred around 0 degree rotation. With screws angled 15 degrees ulna, maximum visualization was between 5 and 10 degrees of pronation. With screws angled 15 degrees radial, maximum visualization was between 5 and 10 degrees of supination. Every 5 degrees of rotation changes the profile of the screw by 0.4 mm.Discussion The diaphysis of the radius becomes approximately trapezoidal distally. Prominent screws that are placed below the “peak” of the trapezoid may appear to be the correct length. Rotating the wrist into pronation or supination to bring the relevant cortex as parallel to the X-ray beam as possible will help to identify if screws are of the correct length. Screws that are prominent in the second compartment may be particularly symptomatic as the tendons here are closely opposed to the bone. We recommend screening for 2 mm diaphyseal screw prominence in neutral, with 10 degrees of pronation and supination.
Keywords: distal radius; screw penetration; X-ray; internal fixation